Iron deficiency and fatigue among adolescents with bleeding disorders. Issue 1 (8th November 2021) - Zia, Ayesha; Stanek, Joseph; Christian‐Rancy, Myra; Savelli, Stephanie; O'Brien, Sarah H.
Abstract: Iron deficiency anemia is associated with heavy menstrual bleeding (HMB) and, by extension, a bleeding disorder (BD). It is unknown if iron deficiency without anemia is associated with a BD in adolescents. Moreover, the threshold of ferritin associated with fatigue in adolescents with HMB is unclear. In this multicenter study, we enrolled adolescents with HMB without BD. Participants underwent BD and anemia work‐up in Young Women's Hematology Clinics and completed the Peds QL™ fatigue scale. BDs were defined as von Willebrand Disease, platelet function defect, clotting factor deficiencies, and hypermobility syndrome. Two hundred and fifty consecutive adolescents were enrolled, of whom 196 met eligibility criteria. Overall, 43% (95% confidence interval: 36%–50%) were diagnosed with BD. A total of 61% ( n  = 119) had serum ferritin levels < 15 ng/mL, 23.5% ( n  = 46) had iron deficiency only, and 37% ( n  = 73) had iron deficiency anemia. Low ferritin or ferritin dichotomized as < 15 or ≥ 15 ng/mL was not associated with BD on univariable analysis ( p  = .24) or when accounting for age, race, ethnicity, body mass index, and hemoglobin ( p  = .35). A total of 85% had total fatigue score below the population mean of 80.5, and 52% ( n  = 102) were > 2 SD (or < 54) below the mean, the cut‐off associated with severe fatigue. A ferritin threshold of < 6 ng/mL had a specificity of 79.8% but a sensitivity of 36% for severe fatigue. In conclusion, iron deficiency without anemia is not a predictor of BD in adolescents with HMB in a specialty setting. Severe fatigue, especially sleep fatigue, is prevalent in adolescents with BD. Ferritin of < 6 ng/mL has ~80% specificity for severe fatigue in adolescents with HMB.